A Liquid Chromatography with Tandem Mass Spectrometry-Based Proteomic Analysis of Primary Cultured Cells and Subcultured Cells Using Mouse Adipose-Derived Mesenchymal Stem Cells - Yoshiki Nakashima; Saifun Nahar; Chika Miyagi-Shiohira; Takao Kinjo; Naoya Kobayashi; Issei Saitoh; Masami Watanabe; Jiro Fujita; Hirofumi Noguchi (Hindawi Limited, 2019)
Adipose-derived mesenchymal stem cells (MSC-ATs) are representative cell sources for cell therapy. However, how cell stress resulting from passage influences the MSC-AT protein expression has been unclear. In this study, a protein expression analysis was performed by liquid chromatography with tandem mass spectrometry (LC-MS/MS) using mouse primary cultured cells (P0) and cells passaged three times (P3) as samples. A total of 256 proteins were classified as cellular process-related proteins, while 179 were classified as metabolic process-related proteins in P0. These were considered to be adaptive responses of the cells to an in vitro environment. However, seven proteins of growth were identified (Csf1, App, Adam15, Alcam, Tbl1xr1, Ninj1, and Sbds) in P0. In addition, four proteins of antioxidant activity were also identified (Srxn1, Txndc17, Fam213b, and Apoe) in P0. We identified 1139 proteins expressed in both P0 and P3 cells that had their expression decreased to 69.4% in P3 cells compared with P0 cells, but 1139 proteins are very likely proteins that are derived from MSC-AT. The function of MSC-ATs was maintained after three passages. However, the LC-MS/MS analysis data showed that the protein expression was degraded after three passages. MSC-ATs retained about 70% of their protein expression ability in P3 cells.